1995
DOI: 10.1007/bf01857704
|View full text |Cite
|
Sign up to set email alerts
|

Do cigarette smokers have unrealistic perceptions of their heart attack, cancer, and stroke risks?

Abstract: This study examined whether perceived risks of heart attack, cancer, and stroke were higher among smokers than nonsmokers; whether smokers were more likely to underestimate these risks; and the demographic correlates of unrealistic risk estimation among smokers. Two thousand seven hundred eight-five patients from 12 North Carolina family practices completed a questionnaire including a health risk appraisal and questions concerning smoking behavior and perceived risks of heart attack, cancer, and stroke. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
92
5
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(111 citation statements)
references
References 12 publications
11
92
5
3
Order By: Relevance
“…Most people believe they are more capable than average and that their chances of a better future are higher than those of others. However, these self-serving biases do not only emerge when people compare themselves to others, but are also present in absolute terms (Weinstein, Rothman, & Klein, 1996); (Strecher, Kreuter, & Kobrin, 1995). Indeed, there is evidence that normal, mentally healthy individuals' perceptions of reality are characterized not by an accurate assessment of their personal qualities, a realistic estimate of their degree of personal control, and a realistic outlook on the future, but are biased and self-serving.…”
Section: The Meaning Of Unrealistic Optimismmentioning
confidence: 99%
See 1 more Smart Citation
“…Most people believe they are more capable than average and that their chances of a better future are higher than those of others. However, these self-serving biases do not only emerge when people compare themselves to others, but are also present in absolute terms (Weinstein, Rothman, & Klein, 1996); (Strecher, Kreuter, & Kobrin, 1995). Indeed, there is evidence that normal, mentally healthy individuals' perceptions of reality are characterized not by an accurate assessment of their personal qualities, a realistic estimate of their degree of personal control, and a realistic outlook on the future, but are biased and self-serving.…”
Section: The Meaning Of Unrealistic Optimismmentioning
confidence: 99%
“…Although less researched, there is also substantial evidence that absolute UO not only exists but is the norm , (Strecher et al, 1995), Coelho (2004)). …”
Section: Brief Overview Of Psychological Evidencementioning
confidence: 99%
“…One other notable quantitative study 15 showed a similar low level of perception. Other studies have shown that smokers underestimate the risks to their health, 16 or understand the well-known connections (for example lung cancer) but not the other health problems. 17 Our study confirms the ignorance of the risks of oral cancer and offers some new insight into the attitudes and perceptions that accompany this.…”
Section: Discussionmentioning
confidence: 97%
“…Un dato interesante es que no hubo diferencias entre fumadores y no fumadores conforme al grado de información recibida en la escuela sobre el tabaco y el daño a su salud. Existe, en este sentido, alguna evidencia de otros estudios de que el aumento de conocimientos impartidos en la escuela no provoca reducción en la tasa de fumadores 9,24,25 . Intimidar a los niños con hechos mórbidos probablemente sea ineficaz.…”
Section: Discussionunclassified